2021
DOI: 10.3390/catal11080975
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Oxidation of Ammonia to Molecular Nitrogen in Water under UV, Vis and Sunlight Irradiation

Abstract: Titanium dioxide-based photocatalysts have been used to perform the photo-oxidation of ammonium/ammonia to molecular nitrogen. Different light sources were employed, i.e., UV, LED visible light and natural sunlight, and their performance was compared in order to understand which setup was the most efficient. It was found that under selected conditions, the LED lamp, in combination with silver-promoted TiO2, was able to push the conversion of ammonium toward 48% after 4 h of reaction time. On the other hand, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…We recently demonstrated that the oxidation of ammonium can occur on the same titania-based catalyst employed so far, and in the same conditions [25,26]; subsequently, a combined photo-treatment was performed to abate, simultaneously, both nitrate and ammonium (Reaction 4).…”
Section: Combined Photo-degradation Under Visible Lightmentioning
confidence: 89%
See 1 more Smart Citation
“…We recently demonstrated that the oxidation of ammonium can occur on the same titania-based catalyst employed so far, and in the same conditions [25,26]; subsequently, a combined photo-treatment was performed to abate, simultaneously, both nitrate and ammonium (Reaction 4).…”
Section: Combined Photo-degradation Under Visible Lightmentioning
confidence: 89%
“…Metal promotion of the catalysts was achieved through wet impregnation [16], which Lastly, a third test was carried out with a constant air supply flowing through the solution. This setup returned a small increase in the reactor performance in the case of photo-oxidation of ammonium [25]. However, Figure 10 clearly highlights a limited effect of this solution, as the conversion is only pushed up to 22%.…”
Section: Materials Preparationmentioning
confidence: 94%
“…We have recently demonstrated that the oxidation of ammonium can occur on the same titania-based catalyst employed so far and in the same conditions [22,23], then, a combined photo-treatment was performed to abate simultaneously both nitrate and ammonium. The ratio between the reactants was set to the stoichiometric and the degradation was performed in three configurations in order to boost the reactions.…”
Section: Comparison Of Different Photocatalystsmentioning
confidence: 89%
“…Lastly, a third test was carried out with a constant air supply flowing through the solution. This setup returned a small increase in the reactor performance in case of photo-oxidation of ammonium [22]. However, Figure 9 clearly highlights a limited effect of this solution, as the conversion is only pushed up to a 22%.…”
Section: Comparison Of Different Photocatalystsmentioning
confidence: 91%
“…The Photo-Fenton reaction was carried out first under visible light in order to optimize all the reaction parameters, since a similar setup was adopted successfully during previous investigations with an azo-type dye. [38] First of all, the impact of the pollutant concentration has been investigated on conversion. Four solutions of DCF in the range 12-100 ppm were prepared and tested with reactor A.…”
Section: Photo-fenton Reactionmentioning
confidence: 99%